Analisis Kebutuhan Pengembangan E-modul untuk Melatih Kemampuan Literasi dan Numerasi Siswa dalam Pembelajaran Sejarah - Saripa Aini; Aisiah Aisiah (Jurusan Sejarah FIS UNP, 2026)
This research is motivated by the low level of students’ literacy and numeracy skills in history learning, which impacts their critical thinking abilities and their capacity to relate historical events to everyday life. The purpose of this study is to analyze the need for developing an e-module teaching material to train students’ literacy and numeracy skills in history learning at SMAN 1 IX Koto Dharmasraya. This study employed a mixed-methods descriptive design with a qualitative approach. The research subjects consisted of a history teacher and 11th-grade students as the target users of the e-module. Data sources were obtained from interviews, observations, and needs analysis questionnaires. Data collection techniques included in-depth interviews with one history teacher, questionnaires distributed to 30 students, and direct observation of the learning process. Quantitative findings showed that students’ literacy and numeracy skills were relatively low. Based on two pre-test items on literacy and numeracy, 43.3% of students answered correctly while 56.7% answered incorrectly. The survey also revealed that the school does not yet have an e-module to train students’ literacy and numeracy skills, and 70% of students expressed the need for an e-module for history learning. Qualitatively, observations and teacher interviews indicated that the teaching materials used are still predominantly in printed form, lack interactivity, and do not adequately support independent learning. Both teachers and students expressed the need for a digital, interactive teaching material that aligns with the Merdeka Curriculum and is capable of enhancing literacy and numeracy skills. The findings also suggest that an e-module integrating text, images, and videos would improve students’ motivation and comprehension.Based on the needs analysis, it can be concluded that developing a history learning e-module is feasible and relevant for implementation, as it supports learning objectives and improves students’ literacy and numeracy skills.